2014
DOI: 10.1002/art.38854
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of a Unique Spleen Tyrosine Kinase Bright Memory B Cell Population in Systemic Lupus Erythematosus

Abstract: Objective. Systemic lupus erythematosus (SLE) is characterized by B cell hyperactivity and autoantibody production. As spleen tyrosine kinase (Syk) is pivotal in B cell activation, these experiments aimed to examine the extent to which Syk was abnormally expressed in SLE B cells and the nature of the B cell subset that differently expressed Syk.Methods. B cells from healthy donors and SLE patients were analyzed by flow cytometry to assess basal expression of Syk and phosphorylated Syk. B cell subsets expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 46 publications
5
47
0
Order By: Relevance
“…Since it has been shown that naive and memory B cells have different BCR activation thresholds , further analyses were performed using conventional CD27− naive and CD27+ memory B cells. Of note, the recently published memory‐like CD27−Syk++ B cell subset was excluded from the CD27− naive B cell compartment and analyzed separately (Supplementary Figure , online at http://onlinelibrary.wiley.com/doi/10.1002/art.39559/abstract). Interestingly, cells from healthy donors, but not those from SLE patients, exhibited increased pSyk (Y 352 ) MFI values upon BCR stimulation in CD27+ versus CD27− B cells (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been shown that naive and memory B cells have different BCR activation thresholds , further analyses were performed using conventional CD27− naive and CD27+ memory B cells. Of note, the recently published memory‐like CD27−Syk++ B cell subset was excluded from the CD27− naive B cell compartment and analyzed separately (Supplementary Figure , online at http://onlinelibrary.wiley.com/doi/10.1002/art.39559/abstract). Interestingly, cells from healthy donors, but not those from SLE patients, exhibited increased pSyk (Y 352 ) MFI values upon BCR stimulation in CD27+ versus CD27− B cells (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…DN B cells are thought to represent a transient memory subset that may originate from incomplete germinal centers or extrafollicular reactions21, providing an expanded source of IgG+ plasmablasts 22. CD27 + and CD27‐ DN class‐switched memory cells share overlapping clones23, and the transition of B cells between these memory pools may be due to downregulation of CD27 secondary to chronic antigen stimulation 24.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β3 has been suggested to be therapeutic in a mouse model of SLE[25], and the findings of this study suggest that TGF-β3 modifying therapy may be therapeutic in human autoimmune diseases with B cell dysregulation. It has been suggested that B cells with increased Syk phosphorylation might be a source for pathogenic plasma cells in SLE[52], and TGF-β3, which inhibits phosphorylation of Syk and ASC differentiation, may be able to inhibit those B cells as well as their differentiation into pathogenic plasma cells.…”
Section: Discussionmentioning
confidence: 99%